The Simulation Strength Analysis on PVC Pipe Blade Propeller Horizontal Axis Wind Turbine with Tip Elbow - Aji Tisa Prayudha; Bagus Wahyudi (Journal of Evrímata: Engineering and Physics, 2024)
Generally, The basic problem of wind energy technology is how to design wind turbines from materials that are easily available in the market, one of the solutions is PVC pipe as a blade material. This material is easily search at building shop . but, it is necessary to analyze the working stress that occurs in PVC blade construction, so that the PVC pipe propeller wind turbine is safe and durrable when applied in the community. The purpose of this study is to determine the effect of wind speed and tip elbow width on working stress. The simulation test method uses Ansys Flow Simulation Software and then the results are exported to Static Simulation to determine the strength of the material. Simulation tests were carried out with wind loads on PVC pipe propellers with wind speeds of 5 m/s, 6 m/s, and 7 m/s and elbow tip widths 100 mm, 110 mm, and 130 mm.